Chloroplast/thylakoid-rich material: A possible alternative to the chemically synthesised flow enhancer polyglycerol polyricinoleate in oil-based systems. (March 2023) - Sutcharit, Poramat; Wattanakul, Jutarat; Price, Ruth; Di Bari, Vincenzo; Gould, Joanne; Yakubov, Gleb; Wolf, Bettina; Gray, David A.
Graphical abstract: Highlights: Chloroplast/thylakoid material helps reduce the Casson yield stress of a chocolate model system. Confocal images indicate that chloroplast membrane material surround sugar particles in an oil-based chocolate model system. Chloroplast/thylakoid material possesses the ability to reduce apparent viscosity of an oil-based system. Chloroplast/thylakoid material aids the flow of an oil-based suspension. Chloroplast/thylakoid material is a potential alternative to chemically synthesized PGPR. Abstract: Chloroplasts are abundant organelles in a diverse range of plant materials; they are predominantly composed of multicomponent thylakoid membranes which are lipid and protein rich. Intact or unravelled thylakoid membranes should, in principle, have interfacial activity, but little has been published on their activity in oil-in-water systems, and nothing on their performance on an oil continuous system. In this work different physical methods were used to produce a range of chloroplast/thylakoid suspensions with varying degrees of membrane integrity. Transmission electron microscopy revealed that pressure homogenisation led to the greatest extent of membrane and organelle disruption compared to less energy intensive preparation methods The ability of the derived materials to modulate the flow behaviour of a chocolate model system (65% (w/w) sugar/ sunflower oil (natural amphiphiles removed) suspension) was investigated by acquiring rheological parameters. All chloroplast/thylakoid preparations reduced yield stress, apparent viscosity, tangent flow point and cross over point in a concentration-dependent fashion, although not as significantly as polyglycerol polyricinoleate applied at a commercially relevant concentration in the same chocolate model system. Confocal laser scanning microscopy confirmed presence of the alternative flow enhancer material at the sugar surfaces. This research reveals that low-energy processing methods that do not extensively disrupt thylakoid membranes are applicable to generating materials with marked capacity to affect the flow behaviour of a chocolate model system. In conclusion, chloroplast/thylakoid materials hold strong potential as natural alternatives to synthetic rheology modifiers for lipid-based systems such as PGPR.